Can Natural Resource Governance Drive Sustainable Economic Development in Small Islands? A Systematic Literature Review - Budiman Budiman; Khairul Mujahidi; Mujahidin Hasanul Bisri; Fety Widianti Aptasari (Westscience Press, 2026)
There has been a growing attention in response to numerous multidimensional development challenges emerging within small island context such as vulnerability, geographic isolation, limited infrastructure, and high dependence on coastal and marine resources. Governance has increasingly arisen as a crucial factor affecting sustainable economic development and community resilience in such island context. This study aims to systematically review the current literature on natural resource governance and sustainable economic development in small islands. In specific, the review examines major research themes, governance approaches, livelihood strategies, and rising research gaps within the literature. This study employed a protocol adopted from PRISMA-based systematic literature review approach using the Scopus database. A total of 1,216 publications were initially identified using predefined search strings, followed by screening and eligibility assessment procedures. 16 articles were included in the final analysis. The findings reveal four dominant themes within the literature: collaborative and multi-scalar governance, blue economy transitions, social capital and islandness, and integrated sustainability frameworks. The review further shows that co-management and decentralized governance approaches positively influence livelihood diversification, fisheries sustainability, tourism development, and community resilience. Fisheries and tourism remain the dominant economic sectors, while alternative livelihoods such as aquaculture, homestay management, and marine creative industries are increasingly promoted to strengthen local economic resilience. Nevertheless, persistent challenges remain significant concerns. This includes elite capture, governance inequality, tourism dependency, and limited quantitative evidence.